Does the corporate governance mechanism impact the sustainability report disclosure? - Nugrahani, Tri Siwi; Nurhayati, Nurhayati (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2023)
Abstract: Companies are required to prepare sustainability reports in conducting business by disclosing economic, social and environmental activities. The company's willingness to disclose sustainability reports to show the company's moral compliance with regulations, care for the environment and society which is currently still interesting to study because disclosure of sustainability reports is still being debated whether it is mandatory or not done by companies. Several factors contributed to this disclosure, such as the board of directors, audit committee and ROA of the 24 companies indexed in SRI-KEHATI during 2017-2021. The results of the study show that institutional ownership and the board of directors affect the disclosure of sustainability reports, but the audit committee does not affect the disclosure of sustainability reports. Keywords: sustainability report, audit committee, board of directors Abstrak: Perusahaan diwajibkan menyusun laporan keberlanjutan dalam menjalankan bisnis dengan mengungkapkan kegiatan ekonomi, sosial, dan lingkungan. Kesediaan perusahaan mengungkapkan laporan keberlanjutan untuk menunjukkan kepatuhan perusahaan secara moral terhadap regulasi, peduli terhadap lingkungan dan masyarakat yang saat ini masih menarik untuk diteliti karena pengungkapan laporan keberlanjutan masih menjadi perdebatan antara wajib atau tidak dilakukan oleh perusahaan. Beberapa faktor turut memengaruhi pengungkapan tersebut, seperti dewan direksi, komite audit dan ROA pada 24 perusahaan yang terindeks dalam SRI-KEHATI selama tahun 2017-2021. Hasil studi menunjukkan kepemilikan institusional dan dewan direksi memengaruhi pengungkapan laporan keberlanjutan, namun komite audit tidak memengaruhi pengungkapan laporan keberlanjutan. Kata kunci: laporan keberlanjutan, komite audit, dewan direksi